Supramolecular motifs in dynamic covalent PEG-hemiaminal organogels - Fox, Courtney H. (Nat Commun, 2015)
Dynamic covalent materials are stable materials that possess reversible behaviour triggered by stimuli such as light, redox conditions or temperature; whereas supramolecular crosslinks depend on the equilibrium constant and relative concentrations of crosslinks as a function of temperature. The combination of these two reversible chemistries can allow access to materials with unique properties. Here, we show that this combination of dynamic covalent and supramolecular chemistry can be used to prepare organogels comprising distinct networks. Two materials containing hemiaminal crosslink junctions were synthesized; one material is comprised of dynamic covalent junctions and the other contains hydrogen-bonding bis-hemiaminal moieties. Under specific network synthesis conditions, these materials exhibited self-healing behaviour. This work reports on both the molecular-level detail of hemiaminal crosslink junction formation as well as the macroscopic behaviour of hemiaminal dynamic covalent network (HDCN) elastomeric organogels. These materials have potential applications as elastomeric components in printable materials, cargo carriers and adhesives.